1991
DOI: 10.1002/hep.1840140525
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity in a rat model caused by orally administered methotrexate

Abstract: We undertook a dose-response study in Wistar rats to develop an animal model for methotrexate hepatotoxicity. Rats were given oral methotrexate in 300, 200, 150 and 100 micrograms/kg/day doses for variable lengths of time. The 300 micrograms/kg/day dose produced systemic toxicity; the animals needed to be killed early, and hepatotoxicity was not observed. The lower doses of methotrexate were tolerated for longer durations and were associated with hepatotoxicity in five of the five rats receiving 200 micrograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The benefits for the inclusion of AHCC in chemotherapy strategy can allow the setting of the effective dosage in clinical practice [48], a view that is consistent with the interest in the economics of chemotherapy [3,4,59,60]. Further, the combination of high-dose MTX with intravenous mercaptopurine is superior to low-dose MTX with mercaptopurine [61][62][63], but it remains equivocal that high-dose MTX produces greater enhancement of thiopurine intracellular accumulation compared with low-dose MTX [22,64]. Mack et al [65] found that low-dose, weekly and subcutaneous MTX administration can induce remission in some pediatric patients with Crohn's disease who fail to adequately respond to other immunomodulator medications.…”
Section: Discussionmentioning
confidence: 83%
“…The benefits for the inclusion of AHCC in chemotherapy strategy can allow the setting of the effective dosage in clinical practice [48], a view that is consistent with the interest in the economics of chemotherapy [3,4,59,60]. Further, the combination of high-dose MTX with intravenous mercaptopurine is superior to low-dose MTX with mercaptopurine [61][62][63], but it remains equivocal that high-dose MTX produces greater enhancement of thiopurine intracellular accumulation compared with low-dose MTX [22,64]. Mack et al [65] found that low-dose, weekly and subcutaneous MTX administration can induce remission in some pediatric patients with Crohn's disease who fail to adequately respond to other immunomodulator medications.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, a single dose of 20 mg/kg MTX was used to induce toxic effects on the liver tissue since higher doses of the drug might have resulted in severe systemic toxicity and early death of animals from other reasons such as acute gastrointestinal injury and bone marrow toxicity. As a result, histopathologically MTX toxicity was determined by focal necrosis areas and multiple hepatocyte loss [38]. This dose, which allowed the animals to survive MTX toxicity, also enabled us to witness the preventive effect of UDCA on MTX injury.…”
Section: Resultsmentioning
confidence: 99%
“…This malabsorption results in weight loss and disturbs the cancer chemotherapy of patients. Additionally, cyclical high doses of MTX, as used for acute leukemia (Hersh et al, 1966;Hall et al, 1991), or the relatively high doses of MTX used to treat severe psoriasis, have been associated with liver hepatotoxicity, including progressive hepatic fibrosis and cirrhosis (Roenigk et al, 1971;Tobias and Auerbach, 1973). Furthermore, MTX can cause increased serum creatinine levels, uremia and hematuria, while its administration in high doses has been reported to cause acute renal failure (Kintzel, 2001).…”
Section: Introductionmentioning
confidence: 98%